Analysis of the Teacher’s Role in Efforts to Emphasize Pancasila Profile Values in Classroom Culture SMK - Prihatiningrum, Meida; Efendi, Agus; Khurniawati, Wiji (Universitas Sebelas Maret, 2023)
Educators must serve as role models for students by highlighting the ideals of the Pancasila student profile through their examples. Teachers who instruct in the classroom can impart this. Instructors serve as role models for moral behavior, modeling moral principles in their interactions and behaviors. Based on the Pancasila profile ideals, students are therefore more likely to emulate and accept the behavior displayed by their teachers. The purpose of this study is to describe two things: 1) how teachers implement Pancasila profile values to help students develop their character and behavior as a class culture; and 2) how they integrate Pancasila student profile values into the cultural context of vocational school classes. This kind of study is qualitative and descriptive. Participants in this study included two teachers one for the basic PPLG skills program and the other for homeroom as well as class X PPLG students. Two participants' in-person interviews, four hours of subject observation, and documentation were employed as the data-gathering methods. The study's findings demonstrate how X PPLG at SMK N Solo uses classroom culture as a platform for character development. Although there is no physical barrier between the teacher and the pupils in this approach, the teacher still serves as the class leader and an example for the students. The instructor highlights the importance of the Pancasila student profile in the learning process. This attempts to mold kids' honorable and moral character.